The architectural design of the natural physics in the Qur’an: analytical study of its objectives and philosophy - Hashi, Abdurezak Abdulahi (International Islamic University Malaysia, 2010)
Numerous Qur’anic verses elucidate the structural design of the celestial bodies of the physical cosmos such as the Sun, the Moon, the Earth, the Stars, and the natural rules (sunan) governing such planets in the space. Though a large portion of the Qur’an illuminates the rules of the natural sciences, including the architectural design of the physical world, however, it emphasizes on the worth of signals beyond the scientific natural sciences. As such, the enduring attractive architectural design of the natural physics, the diversity of its subject matter and the expediency of its environmental climate, in the Qur’anic view, are not without philosophy and aim. Besides the functional consistency of the natural physics to serve humanity (taskhÊr), according to the Qur’an, the rules of nature are ayÉt, i.e., signboards, which indicate to ultimate destinations or goals. Hence, the architectural design of the natural physics is both purposive and evocative. Therefore, philosophy of natural physics, which is the study of the philosophical questions underlying the cosmological universe, is a field which the Qur’an required man to reflect upon. Similarly, scholars of philosophy of science agree on the necessity of exploring not only the sciences of the natural world but also its metaphysical indications, objectives and implications. This is because of the fact that, scientific findings and statements are no longer merely neutral accounts without meaningful signals and philosophy. Through analytical and textual methods, this paper attempts to examine the philosophy and objectives of the architectural design of natural physics from the Qur’anic perspective.